High-School Football and Midlife Brain Health Problems. Issue 2 (March 2022) - Iverson, Grant L.; Merz, Zachary C.; Terry, Douglas P.
Abstract : Objective: To examine whether middle-aged men who played high-school football experience worse mental health or cognitive functioning than men who did not play high-school football. Design: Cross-sectional cohort study. Setting: Online survey completed remotely. Participants: A total of 435 men between the ages of 35 and 55 completed the study, of whom 407 were included in the analyses after excluding participants who answered embedded validity items incorrectly (n = 16), played semiprofessional football (n = 2), or experienced a recent concussion (n = 10). Assessment of Risk Factors: Self-reported high school football participation, compared with those who played contact sports, noncontact sports, and no sports. Main Outcome Measures: A lifetime history of depression or anxiety; mental health or cognitive problems in the past year; current depression symptoms, and post–concussion-like symptoms. Results: Middle-aged men who played high-school football did not have a higher prevalence of being prescribed medication for anxiety or depression or receiving treatment from a mental health professional. Similarly, there were no significant differences between groups on the rates in which they endorsed depression, anxiety, anger, concentration problems, memory problems, headaches, migraines, neck or back pain, or chronic pain over the past year. A greater proportion of those who played football reported sleep problems over the past year and reported being prescribed medication for chronic pain and for headaches. Conclusions: Men who played high-school football did not report worse brain health compared with those who played other contact sports, noncontact sports, or did not participate in sports during high school.